Considerations in glaucoma therapy: fixed combinations versus their component medications - Eve J Higginbotham (Dove Medical Press, 2009)
Eve J HigginbothamMorehouse School of Medicine, Atlanta, GA, USAAbstract: Fixed combinations of medications that lower intraocular pressure (IOP) are increasingly used in the treatment of glaucoma and ocular hypertension and offer several potential advantages over combined use of the separate component medications including enhanced convenience, improved adherence, reduced exposure to preservatives, and possible cost savings. This review aims to examine the current role of IOP-lowering fixed combinations in disease management. The results of studies that compared the efficacy and safety of IOP-lowering fixed combinations with their component medications are summarized, including those fixed combinations that consist of a prostaglandin analog and timolol. The fixed combinations currently available for use in the United States are fixed-combination dorzolamide/timolol (FCDT) and fixed-combination brimonidine/timolol (FCBT). Both of these fixed combinations reduce IOP more effectively than their component medications used separately as monotherapy. FCBT therapy also demonstrates a more favorable safety profile and reduced ocular allergy compared to monotherapy with brimonidine, a component medication. Few studies have directly compared the efficacy and safety of FCDT and FCBT, but available evidence suggests that FCBT is at least as effective as FCDT in lowering IOP and is more comfortable and better tolerated. Additional studies are needed to further evaluate the comparative efficacy and tolerability of FCDT and FCBT in the management of glaucoma and ocular hypertension.Keywords: glaucoma, intraocular pressure, fixed combination, adherence, brimonidine